Workplace Well-Being in Manufacturing Organizations in Nigeria: Do Employee Green Behavior, Core Self-Evaluations and Empowering Leadership Matter? - Edosomwan, Henry Samuel; Oguegbe, Tochukwu Matthew; Joe-Akunne, Chiamaka Ogechukwu (International Journal of Occupational Safety and Health, 2023)
Introduction: Workplace well-being has become a key issue in organizational behavior literature because of the impact it has on various outcomes in the organization. Consequent to the aforementioned, this study investigated three antecedents (employee green behavior, core self-evaluation, and empowering leadership) of Workplace well-being in manufacturing organizations in Nigeria. Methods: A quantitative cross-sectional survey and the correlational design were adopted to investigate the direct relationship the three predictor variables (employee green behavior, core self-evaluation, and empowering leadership) have with workplace well-being. Data were collected from 201 employees working in manufacturing organizations in Lagos State, Nigeria using systematic sampling. The participants comprised 124 males and 77 females with a mean age of 31.43 years and a standard deviation of 5.87. Four standardized and psychometrically sound instruments were used for collecting data while regression analysis was used in testing the hypotheses via the IBM SPSS statistics version 25. Results: The results of the study indicated that employee green behavior, core self-evaluations, and empowering leadership positively and significantly predicted workplace well-being in manufacturing organizations. Conclusion: This study provided valuable contributions to the antecedents of workplace well-being. Based on the outcome of the study, it is safe to say that workplace well-being has a link with an individual (employee green behavior and core self-evaluations) and interpersonal factors (empowering leadership) in the organization.